Gaya Bahasa dalam Syair Ikhtārī Karya Nizar Qabbani: Studi Stilistika - Miftahul Ilmi (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2021)
This research aims to reveal how the style of language in the poem Ikhtārī written by Nizar Qabbani. This study used a descriptive qualitative method. The research uses the five levels of stylistic analysis theory by Syihabuddin Qalyubi. The results of this study there is a style of language based on the level in stylistic anaysis, among which is (1) Muhtawiyāt al-ṣauti: repetition of the sound is kasrah at the end of the sentence, ṣawāmit mukarrarah (ra), (2) Muhtawiyāt al-naḥwi: Taqdīmul khabar ‘alā mubtada’ (Prioritizing khabar above mubtada’), 'Aṭaf ma'ṭūf, (3) Mustawā al-dālali: synonyms of the word ukminu, ṣadrun, imra'atun, (4) Mustawā al-ṣuwari: tasybīh, nidā'.